Impact of Fiscal Policy on Balance of Payments in Nigeria (Journal of Management and Social Sciences, 2018)
This study investigates the impact of fiscal policy on balance of payments adjustmentin Nigeria within the periods, 1981-2015. Using the bound testing approach, the studyestablished the relationship that exists among fiscal policy instruments (tax andgovernment expenditure), investment, output and balance of payments adjustment inNigeria. The result revealed that in the long-run, government spending, investment andoutputs have positive impact on balance of payments adjustment in Nigeria. However,tax revenue had negative impact on balance of payments in Nigeria. The high deficitfinance by the Nigerian government where government spending is greater than taxrevenue in most of the years considered had sustained the current account surplus inthe country. Therefore, expansionary policies on fiscal policy measures should beencouraged as they play vital role for the enhancement of balance of payments inNigeria.Keywords Tax, government spending, investment, income, current account balance